Increased expression of multidrug resistance related proteins Pgp, MRP1, and LRP/MVP occurs early in colorectal carcinogenesis. Issue 6 (1st June 1999) - Meijer, G A; Schroeijers, A B; Flens, M J; Meuwissen, S G; van der Valk, P; Baak, J P; Scheper, R J
Abstract : AIM: To analyse the expression of multidrug resistance (MDR) related proteins at different steps in colorectal carcinogenesis. METHODS: The presence of three MDR related proteins (Pgp, MRP1, and LRP/MVP) was studied by means of immunohistochemistry in normal, adenomatous, and malignant colorectal epithelium. Formaldehyde fixed, paraffin embedded tissue sections of 17 samples of colorectal tissue were used (normal mucosa, n = 4; adjacent mucosa, n = 5; adenoma, n = 5; carcinoma, n = 3). RESULTS: For all three proteins, expression was found in the surface epithelium and the upper parts of the crypts in normal colon. In the adenomas, staining was seen along the complete length of the crypts. In the carcinomas analysed, all epithelium showed positive staining. Mucosa adjacent to either carcinoma or adenoma showed staining patterns mostly resembling those of normal mucosa, but sometimes some extension of staining was seen along the crypt. CONCLUSIONS: These proteins already show increased expression in the adenoma stage. In the absence of adequate mucin production in adenomas, MDR related proteins could be an important factor in protecting the epithelium against further environmentally induced genetic damage. This could be one of the reasons why only about 5% of colorectal adenomas will actually progress to carcinomas.